2005
DOI: 10.1097/01.sla.0000167926.60908.15
|View full text |Cite
|
Sign up to set email alerts
|

The Modern Abdominoperineal Excision

Abstract: Patients treated by APR have a higher rate of CRM involvement, a higher LR, and poorer prognosis than AR. The frequency of CRM involvement for APR has not diminished with TME. CRM involvement in the APR specimens is related to the removal of less tissue at the level of the tumor in an APR. Where possible, a more radical operation should be considered for all low rectal cancer tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(66 citation statements)
references
References 24 publications
1
59
0
1
Order By: Relevance
“…Previous studies of risk factors for circumferential resection margin positivity have focused on tumor factors such as T and N categories, tumor size and location, vascular invasion, and the need for abdominoperineal resection. 14,2022 Other studies have reported associations between higher provider and hospital volumes and improved outcomes for oncologic procedures. 2325 In the present analysis, we have identified additional patient and tumor factors associated with underlying risk for margin-positive resection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of risk factors for circumferential resection margin positivity have focused on tumor factors such as T and N categories, tumor size and location, vascular invasion, and the need for abdominoperineal resection. 14,2022 Other studies have reported associations between higher provider and hospital volumes and improved outcomes for oncologic procedures. 2325 In the present analysis, we have identified additional patient and tumor factors associated with underlying risk for margin-positive resection.…”
Section: Discussionmentioning
confidence: 99%
“…The most common site of metastasis was the liver (40%), followed by the lungs (30%), peritoneal seedling (20%), and the brain (10%). The volume of tumors can be reduced by preoperative radiochemotherapy, which also induces downstaging, facilitates surgical resection (10,27), and prevents the distal intramural spread of the tumor, thereby decreasing the surgical distal margin and perirectal lymph node. The technique that allows us to obtain sufficient distal margin in all patients is called transanal intersphincteric resection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Marr et al38 reported that in the linear dimension of transverse slices of tissue containing the tumor, the median, posterior, and lateral measurements were smaller in the APR than the AR. He observed that APR specimens with a histologically-positive CRM (Circumferential Resection Margin) had a smaller area of tissue outside the muscularis propria compared to CRM-negative APR specimens.…”
Section: Perineum Dissection During Abdominoperineal Resectionmentioning
confidence: 99%